COVID-19: A Political Virus? VOX’s Populist Discourse in Times of Crisis - Olivas Osuna, José Javier; Rama, José (Frontiers in Political Science, 2021)
Spain has been one of the hardest hit countries by the COVID-19 pandemic, and this crisis presented a window of opportunity for VOX, as it has for other far right parties, to raise its visibility as opposition force. This paper investigates whether the discourse of VOX has evolved during the pandemic and affected the political dynamics in Spain. This article proposes a new multidimensional strategy to measure the degree of populism in political communications, via quantitative and qualitative content analysis. It dissects the parliamentary speeches of the leader of VOX, Santiago Abascal, in the debates for the approval and extension of the “state of alarm” to fight against COVID-19 between March and June 2020. In order to assess the changes and relative intensity of populist features in Abascal’s parliamentary speeches we compared them with his speech during Pedro Sánchez’s investiture session as the Spanish President of the Government, in January 2020, and VOX’s latest political manifestos—2019 European and Spanish General Elections—, as well as with speeches of the representatives of the five main parties and coalitions during the COVID-19 debates in the Spanish Congress.Our paper shows that populists’ discourses are context-dependent and that their performances are not only shaped by crisis but also constitutive of crisis. The density of populist references in Abascal’s speeches grew steadily during the period analysed. Morality and antagonism overshadowed sovereignty and society as key populist attributes, and the tone of the discourse became increasingly hyperbolic. Moreover, Abascal’s discursive performances had a sort of contagion effect in other parties in the parliamentary sessions studied. People’s Party (Partido Popular–PP) leader Pablo Casado chose to follow VOX and harshly criticized the government, meanwhile the discourses of the speakers of Together We Can (Unidas Podemos–UP) and Catalan Republican Left (Esquerra Republicana de Catalunya–ERC), adopted a demonizing rhetoric against VOX and PP also grounded on a populist logic of articulation. This polarizing dynamic between competing Manichean discourses contributed to reinforce the sense of crisis by adding a political dimension to the already existing health and economic problems.